A V‐Shaped Polyaromatic Amphiphile: Solubilization of Various Nanocarbons in Water and Enhanced Photostability. Issue 36 (21st July 2015) - Kondo, Kei; Akita, Munetaka; Nakagawa, Takafumi; Matsuo, Yutaka; Yoshizawa, Michito
Abstract Nanocarbons are synthetic carbon‐rich compounds with polyaromatic frameworks that have lately attracted attention as emerging functional materials. However, their extreme hydrophobicity and aggregation peculiarity, besides their shape and size diversities, precluded their study in solution, especially in "green" water. More convenient and general solubilizing methods of nanocarbon frameworks are required by using non‐covalent supramolecular interactions. Here we report a protocol for solubilizing a wide range of nanocarbons, that is, fullerenes (C60, C70, C84, and C120), polyarenes (tetracene, pentacene, perylene, coronene, and hexabenzocoronene), and carbon nanotubes (single‐walled and multi‐walled CNTs), in water through manual grinding with V‐shaped polyaromatic amphiphiles. The obtained aqueous nanocomposites are composed of nanocarbons encircled by the polyaromatic frameworks of the amphiphiles through multiple aromatic–aromatic interactions. Notably, the encapsulated photosensitive nanocarbons, such as tetracene, pentacene, and fullerene dimer, exhibit unusual stability toward UV/Vis light.